2022
DOI: 10.3390/cancers14071853
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Potential of Post-Fermentation Media and Cell Extracts of Probiotic Strains: An In Vitro Study

Abstract: Background: Lactic acid bacteria (LAB), many of which are probiotics, can produce health-promoting metabolites (postbiotics). Purpose: To assess the mechanism of antiproliferative action of postbiotics, post-fermentation media (PFM) and cell extracts (CEs) of several strains of LAB were studied against colon (Caco-2), and cervix (HeLa) cancer cell lines, as well as normal intestine (IEC-6) cells, were used as a comparison. Methods: Postbiotics of various LAB (n = 39) were screened for their antiproliferative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In turn, postbiotics are bioactive compounds secreted by probiotics in the fermentation process [25]. According to the definition given on the experts' panel in 2021, a postbiotic is "a preparation of inanimate microorganisms and/or their components that confers a health benefit on the host" [26,27]. Postbiotic compounds include, but are not limited to, short-chain fatty acids (SCFAs), functional proteins, metabolites, enzymes, bacteriocins, extracellular polysaccharides (EPS), and microbial cell fractions (e.g., cell walls, cell membranes).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, postbiotics are bioactive compounds secreted by probiotics in the fermentation process [25]. According to the definition given on the experts' panel in 2021, a postbiotic is "a preparation of inanimate microorganisms and/or their components that confers a health benefit on the host" [26,27]. Postbiotic compounds include, but are not limited to, short-chain fatty acids (SCFAs), functional proteins, metabolites, enzymes, bacteriocins, extracellular polysaccharides (EPS), and microbial cell fractions (e.g., cell walls, cell membranes).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, significantly higher cytotoxicity was observed after the combination of nisin with doxorubicin, suggesting a synergistic effect of these chemicals on cell viability [ 83 ]. According to Nowak et al, the cytotoxicity of the LAB post-fermentation media depended on their concentration and reached higher values than the cytotoxicity demonstrated by the cell extracts, which also strongly affected the viability of Caco-2 cells [ 31 ]. Chuah et al determined the selective cytotoxic effect of postbiotic LAB metabolites produced by 6 strains of L. plantarum on various cancer cell lines [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acids were analyzed qualitatively and quantitatively by comparing standard solutions with CFS from LAB. The chromatographic separation, absorbance measurement, and calculation of organic acid concentrations were determined according to the methodology presented in our previous publication [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…To more specifically modulate the recipient’s gut microbiota to more efficiently improve their response to other forms of cancer treatment, it has been envisaged to more purposefully combine one or several microorganisms into a single formulation. 372 Existing evidence has demonstrated that certain microbial consortia could indeed boost the efficacy of conventional cancer therapies. In an RCT evaluating metastatic renal cell carcinoma, patients treated with both ICIs and CBM588, a bifidogenic live bacterial product, were found to have significantly longer progression-free survival and higher response rates to ICIs than patients treated with ICIs alone, 70 demonstrating that bifidogenic live bacterial products may be able to promote the anticancer effects of ICIs on metastatic renal cell carcinoma.…”
Section: Cancer-related Microorganisms and Effectorsmentioning
confidence: 99%